Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040445
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature CVD Grown Graphene for Highly Selective Gas Sensors Working under Ambient Conditions

Abstract: Abstract:In this paper we report on gas sensors based on graphene grown by Chemical Vapor Deposition at 850 °C. Mo was used as catalyst for graphene nucleation. Resistors were directly designed on pre-patterned Mo using the transfer-free process we recently developed, thus avoiding films damage during the transfer to the target substrate. Devices operating at room temperature and relative humidity set at 50% were tested towards NO2. The sensors resulted to be highly specific towards NO2 and showed current vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Decreasing the anneal time from 90 min down to 5 min on Sample 1 still shows MLG growth with a quality similar to that reported in figure 6 for 90 min anneal. At a reduced anneal temperatures of 800 °C, we no longer observe any growth which is similar to our observations on CVD based MLG [34]. Figure 7 shows the comparison between the various anneal temperatures and times.…”
Section: Resultssupporting
confidence: 87%
“…Decreasing the anneal time from 90 min down to 5 min on Sample 1 still shows MLG growth with a quality similar to that reported in figure 6 for 90 min anneal. At a reduced anneal temperatures of 800 °C, we no longer observe any growth which is similar to our observations on CVD based MLG [34]. Figure 7 shows the comparison between the various anneal temperatures and times.…”
Section: Resultssupporting
confidence: 87%
“…Figure 5 adsorption of water molecules, differently from what occurs towards other analytes. In previous reports, we have demonstrated that MLG is three orders of magnitude (~6%-7%/ppm) more sensitive towards NO2 compared to RH [23]. MLG has also higher sensitivity upon ammonia (NH3) (~0.01%/ppm) than RH, provided that our material is not such affine to NH3 [22].…”
Section: Resultsmentioning
confidence: 63%
“…In this framework, here, we demonstrate that relatively defective and rough multi-layered graphene (MLG) is insensitive to humidity, while having previously proved that the same MLG is a very promising sensing material upon other analytes [21][22][23]. In those reports, we demonstrated that MLG shows a sensitivity up to~6%-7%/ppm towards nitrogen dioxide (NO 2 ).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This characteristic feature is related to the growing process, which can cause intrinsic defects due to the reconstruction of the lattice in non-hexagonal rings, such as pentagons, hexagons, and heptagons [21]. Thus, it is likely that such defects, which are intrinsically ascribed to the layer synthesis, together with the edge defects, are responsible for the poor reactivity to relative humidity while enhancing the reactivity to some volatile organic compounds, such as ethanol for example [22,23].…”
Section: Resultsmentioning
confidence: 99%